Indigenous Sanctions vs. Universal Human Rights: Deciphering the Epistemic Clash in the Codification of Customary Penal Systems - Muhammad Wahid Cahyana; Ismawati Ismawati; Rashid Rahman (Islamic Studies in the World, 2026)
Background. Legal pluralism has intensified global debates concerning the relationship between indigenous customary justice systems and universal human rights norms. Efforts to codify customary penal systems increasingly generate tensions regarding cultural autonomy, legal legitimacy, and human dignity. Indigenous sanctions are often grounded in communitarian conceptions of justice that emphasize restoration, reconciliation, and collective responsibility, whereas international human rights frameworks prioritize individual rights, procedural fairness, and equality before the law. Purpose. This study aims to examine the epistemic foundations underlying these tensions and explore how competing legal knowledge systems influence the codification of customary penal systems. Method. A qualitative socio-legal research design was employed through document analysis, comparative case examination, thematic coding, and interpretive analysis of legal texts, policy documents, judicial decisions, and scholarly literature concerning customary law and human rights. Results. Findings reveal that conflicts emerging during codification processes are primarily epistemological rather than purely legal in nature. Differences in conceptions of justice, authority, accountability, and social order significantly shape perceptions of legitimacy among indigenous communities, state institutions, and human rights actors. Participatory legal reforms incorporating indigenous perspectives were found to reduce normative tensions and improve acceptance of codified legal frameworks. Conclusion. The study concludes that sustainable legal integration requires recognition of epistemic diversity alongside commitments to fundamental human rights protections. Constructive dialogue between indigenous legal traditions and universal human rights frameworks offers a pathway toward more inclusive and culturally responsive legal governance in pluralistic societies.